Optimal Contracting with Moral Hazard and Cascading - Khanna, Naveen (Review of Financial Studies, 1998)
Journal Article Optimal Contracting with Moral Hazard and Cascading Get access Naveen Khanna Naveen Khanna Michigan State University Address correspondence to Naveen Khanna, 315 Eppley, Eli Broad College of Business, Michigan State University, East Lansing, MI 48824-1121, or e-mail: khanna@pilot.msu.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 11, Issue 3, July 1998, Pages 559–596, https://doi.org/10.1093/rfs/11.3.559 Published: 03 June 2015